PENGARUH LINGKUNGAN KELUARGA DAN PRESTASI BELAJAR SISWA TERHADAP MINAT UNTUK MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA KELAS XII IPA DI SMA PGRI JAYAPURA - Dwi Nuryaningsi; Maik Akobiarek; Leonardo Elisa Aisoi (Universitas Cenderawasih, 2024)
This research aims to determine the influence of the family environment on interest in continuing studies to higher education in class determine the influence of the family environment and student learning achievement on interest in continuing their studies to higher education in class XII Science students at SMA PGRI Jayapura. This research was conducted at SMA PGRI Jayapura in the even semester of the 2017/2018 academic year. The population in this study was 58 students in class XII Science at SMA PGRI Jayapura. Data collection techniques use questionnaires and documentation. The data analysis method used is multiple regression.The results of this research show a partial test: (1) there is an influence of the family environment on the interest in continuing their studies to higher education in class XII Science students at SMA PGRI Jayapura. (2) there is no influence of learning achievement on interest in continuing studies to higher education in class XII Science students at SMA PGRI Jayapura. Simultaneously: (3) There is an influence of the family environment and learning achievement on the interest in continuing their studies to higher education in class XII Science students at SMA PGRI Jayapura. Keywords : Family Environment, Learning Achievement, Further Studies, Interests